Exercise training improves functional walking capacity and activity level of Nigerians with chronic biventricular heart failure - O.A. Ajiboye, PhD; C.N. Anigbogu, PhD; J.N. Ajuluchukwu, MD; S.I. Jaja, PhD (World Scientific Publishing, 2015)
Background: Exercise training (ET) has been recommended as an adjunctive therapy in chronic heart failure but the role of ET in people with biventricular heart failure (BVF) has not been explored in Nigeria. Objective: This study aimed to investigate the role of ET on functional walking capacity and activity level of Nigerians with BVF. Methods: Sixty-six patients with chronic BVF in New York Heart Association Class II and III (mean age 54.0 ± 1.6 years) recruited from a Nigerian tertiary hospital participated in the study. They were randomized into either the exercise group or control group. These patients were on their prescribed medications and underwent education/counselling sessions. In addition, patients in the exercise group performed aerobic and resistance training thrice weekly for 12 weeks. Functional walking capacity was assessed using the 6-minute walk test, oxygen consumption was estimated using the Duke Activity Status Index questionnaire while the Veterans' Specific Activity questionnaire was used to assess the activity level. Results: The exercise group had significant improvements in all components of functional walking capacity and activity level. No significant improvement was observed in controls (p < 0.05). Conclusion: Supervised and structured ET is safe and beneficial for patients with BVF.